Sodium intake beliefs, information sources, and intended practices of endurance athletes before and during exercise - McCubbin, A. J.; Cox, G. R.; Costa, R. J. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
There is little information describing how endurance athletes perceive sodium intake in relation to training and competition. Using an online questionnaire, this study assessed the beliefs, information sources, and intended practices regarding sodium ingestion for training and competition. Endurance athletes (n = 344) from six English-speaking countries completed the questionnaire and were included for analysis. The most cited information sources were social supports (63%), self-experimentation (56%), and media (48%). Respondents generally believed (>50% on electronic visual analog scale) endurance athletes require additional sodium on a daily basis (median 67% [interquartile range: 40-81%]), benefit from increased sodium in the days preceding competition (60% [30-77%]), should replace sodium losses during training (69% [48-83%]) and competition (74% [54-87%]), and would benefit from sweat composition testing (82% [65-95%]). Respondents generally believed sodium ingestion during endurance exercise prevents exercise-associated muscle cramps (75% [60-88%]) and exercise-associated hyponatremia (74% [62-89%]). The majority (58%) planned to consciously increase sodium or total food intake (i.e., indirectly increasing sodium intake) in the days preceding competition. Most (79%) were conscious of sodium intake during competition, but only 29% could articulate a specific intake plan. A small minority (5%) reported using commercial sweat testing services, of which 75% believed it was beneficial. We conclude that endurance athletes commonly perceive sodium intake as important for their sporting activities. Many intend to consciously increase sodium intake in the days preceding and during competition, although these views appear informed mostly by nonscientific and/or non-evidence-based sources.